2022
DOI: 10.3390/toxins14060375
|View full text |Cite
|
Sign up to set email alerts
|

The Phospholipase Activity of Ammodytoxin, a Prototype Snake Venom β-Neurotoxin, Is Not Obligatory for Cell Internalisation and Translocation to Mitochondria

Abstract: β-Neurotoxins are secreted phospholipase A2 molecules that inhibit transmission in neuromuscular synapses by poisoning the motor neurons. These toxins specifically and rapidly internalise into the nerve endings of motor neurons. Ammodytoxin (Atx) is a prototype β-neurotoxin from the venom of the nose-horned viper (Vipera ammodytes ammodytes). Here, we studied the relevance of the enzymatic activity of Atx in cell internalisation and subsequent intracellular movement using transmission electron microscopy (TEM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Like Atx, a snake venom orthologue of rGIIA, rGIIA was also able to reach the mitochondria of the PC12 cells from the media ( Supplementary Figure S1 ). Just recently, it was reported that Atx was able to enter the mitochondria of the PC12 cells independently of its enzyme activity [ 14 ]; so, we also tested such an ability for the enzymatically inactive mutant of rGIIA, rGIIA(D49S). The mutant was fluorescently labeled with 546 Alexa and added to the PC12 cells in a culture.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Like Atx, a snake venom orthologue of rGIIA, rGIIA was also able to reach the mitochondria of the PC12 cells from the media ( Supplementary Figure S1 ). Just recently, it was reported that Atx was able to enter the mitochondria of the PC12 cells independently of its enzyme activity [ 14 ]; so, we also tested such an ability for the enzymatically inactive mutant of rGIIA, rGIIA(D49S). The mutant was fluorescently labeled with 546 Alexa and added to the PC12 cells in a culture.…”
Section: Resultsmentioning
confidence: 99%
“…This activity of GIIA is obviously independent of its phospholipase activity, as is its cell internalization. Indeed, rGIIA(D49S) added to the medium containing PC12 cells passed through the plasma membrane and colocalized with mitochondria like Atx(D49S) [ 14 ]. The effect of rGIIA(D49S) on the cells in the culture was indicated by a slightly reduced TMRM fluorescence intensity, indicating a reduction in the MMP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations